Newborn Screening for X-Linked Adrenoleukodystrophy: The Initial Illinois Experience - Barbara K. Burton; Rachel Hickey; Lauren Hitchins; Vera Shively; Joan Ehrhardt; Laura Ashbaugh; Yin Peng; Khaja Basheeruddin (MDPI AG, 2022)
X-linked adrenoleukodystrophy (X-ALD) is a genetic neurodegenerative disorder with an approximate incidence of 1 in 14,700 births. Both males and females are affected. Approximately one-third of affected males develop childhood cerebral adrenoleukodystrophy, which progresses rapidly to severe disability and death. In these cases, early surveillance and treatment can be lifesaving, but only if initiated before the onset of neurologic symptoms. Therefore, X-ALD was added to the Recommended Uniform Screening Panel. We report outcomes of the initial screening of approximately 276,000 newborns in Illinois. The lipid C26:0 lysophosphatidylcholine (C26:0-LPC) was measured in dried blood spots (DBS) using liquid chromatography with tandem mass spectrometry. Results ≥ 0.28 µmol/L were considered screen positive. Of 18 screen positive results detected, 12 cases were confirmed. Results were reported as borderline if initial and repeat analyses were ≥0.18 and <0.28 µmol/L. Of the 73 borderline screen results, 57 were normal after analysis of a second sample. Five X-ALD cases were identified from borderline screens. Newborn screening of X-ALD was successfully implemented in Illinois, and results were comparable to reports from other states. Early identification of infants with this potentially life-threatening disorder will significantly improve outcomes for these children.